2014
DOI: 10.1007/s11695-014-1179-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Mineral Density After Sleeve Gastrectomy or Gastric Bypass: Relationships with Variations in Vitamin D, Ghrelin, and Adiponectin Levels

Abstract: One year after gastric bypass, bone mineral density was significantly affected, mainly at the femoral neck. Decreases in bone mineral density were more dramatic among patients who had greater baseline BMD and greater reduction in ghrelin concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 39 publications
4
64
3
1
Order By: Relevance
“…Although RYGB and SG are highly effective in causing sustained weight loss, our results add to a body of literature that suggests that bone loss may in fact be the major metabolic complication of such surgeries (2, 46, 1115, 32). In particular, our study shows that RYGB and SG, the two most popular forms of bariatric surgery, are both associated with declines in areal and volumetric BMD at the lumbar spine, and that RYGB is also associated with a decline in total hip areal and volumetric BMD at 12 months.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Although RYGB and SG are highly effective in causing sustained weight loss, our results add to a body of literature that suggests that bone loss may in fact be the major metabolic complication of such surgeries (2, 46, 1115, 32). In particular, our study shows that RYGB and SG, the two most popular forms of bariatric surgery, are both associated with declines in areal and volumetric BMD at the lumbar spine, and that RYGB is also associated with a decline in total hip areal and volumetric BMD at 12 months.…”
Section: Discussionmentioning
confidence: 50%
“…To date, studies comparing RYGB and SG and their effects on BMD by DXA have shown conflicting results. Two studies of patients undergoing RYGB and SG suggested accelerated bone loss at the lumbar spine and hip after RYGB compared to SG, although the differences were not significant (11, 15), while another study showed no change in lumbar spine BMD but a greater decline in hip BMD following RYGB compared to SG (12). These findings are consistent with our study, which found trends for greater femoral bone loss after RYGB than SG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin is involved in energy homeostasis and insulin sensitivity. A literature review shows that adiponectin is almost universally increased after bariatric surgery or medical weight loss (17, 19, 23, 29, 34, 41, 45, 47, 50, 55, 6484). Moreover, no study showed an increase in adiponectin due to a given procedure not also possibly explained by weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…25 Much has been hypothesized about the interplay of adiponectin, vitamin D and PTH in energy and calcium balance, but few direct adiponectin-related mechanisms have been identified. 26, 27 Adiponectin action has been mechanistically tied to another endocrine factor, FGF21, and its co-receptor, beta-klotho in liver and adipose tissue. 28, 29 We therefore hypothesized that a relationship between adiponectin, bone-derived FGF23 and its kidney-based co-receptor alpha-Klotho (here simply referred to as Klotho) exists and may be responsible for the dysregulated calcium and phosphate balance observed under conditions of high adiponectin levels, thereby modulating the cytoprotective effects of Klotho, and contributing to bone disease in CKD.…”
Section: Introductionmentioning
confidence: 99%